Education Can Improve Community Participation in the Control of Dengue Haemorrhagic Fever in Cicadas and Babakan Penghulu Village, Bandung City, a Case of Participation Measurement Using the Method of Arnstein - Sri Indriyani; Juli Soemirat (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: According to the Ministry of Health, cases of dengue haemorrhagic fever (DHF) increased from 2 to 34 provinces during 46 years, hence, Indonesia had not been able to control DHF. While specific drugs and vaccines against DHF virus are not yet available, the only way to control DHF is by controlling the vector. Sustainable Development Goals (SDG's) program on vector borne diseases requires a reduction of mortality by 75% and incidences by 60% in 2030. Vector control in Indonesia is being done through community participation such as draining, closing, and recycling used goods, and activities to avoid mosquito bites known as "3M Plus”. There is, therefore, a need to measure the degree of community participation being done so far and the factors that influence it. Methods: Measurement of the level of community participation was carried out using the method of Arnstein (A Ladder of Citizen Participation). The variables used in the measurements were the understanding, the benefits, and the implementation of participation in the 3M Plus program. The research location was chosen based on the mapping of areas with high and low DHF incidence. Samples were determined by the Slovin method, stratified by permanent, semi permanent, and non permanent houses. Data collection were carried out by interviews. Factors that influence community participation are measured by statistical tests, namely multiple linear regression. Result and Discussion: The largest level of community participation is still at the level of manipulation (no participation) with a percentage of 50.5% in Cicadas and 65.6% in Babakan Penghulu; statistical analysis shows that education education had a significant influence in both villages. Conclusion: There has been no actual community participation yet. Therefore, comprehensive education and counseling are needed for the entire community. Considering that breeding places are not only found in settlements, it is necessary to collaborate with other sectors, such as agriculture, environment, fisheries, irrigation, finance, tourism, transportation, urban areas, livestock, forestry, and infrastructure.